Homofobia y expresiones de la homosexualidad en la vejez: un acercamiento a la película mexicana Cuatro lunas - Dr. Alejandro JIMÉNEZ ARRAZQUITO (Fonseca, Journal of Communication, 2023)
Contemporary Mexican audiovisual productions that feature homosexual men usually present them as adolescents or young characters and tend to refuse the representation of older men's experiences. In social reality, this concealment contributes to the absence of elderly homosexual men in the public agenda, which can lead to their isolation and psychological suffering, and drag them back to the closet.